Rorty: Language, Metaphor and Politics - Figueroa, Maximiliano (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This article presents, in its fundamental aspect, the theory of language of American pragmatist Richard Rorty, its construction from the reception and interpretation of Donald Davidson’s linguistic philosophy and his conception of metaphor. The central tenets are developed and weighted as follows: contingency and historicity of language as conditions that prevent conception acquitted of any contextual link, holistic consideration of language games as a privilege justification for the pragmatic assessment evaluation, the non-cognitive dimensions of language that opens in a special way, metaphor, and, finally, projections or implications for human communication and the construction of a socio-political, pluralist, dialogic and imaginative democratic order.